Medical Records as Evidence of the Performance of Obligations in Therapeutic Agreements: An Analysis of Legal Certainty and Legal Protection in Indonesian Hospital Services - Dewi Indrayani; Prassetyo Edi (Siber Nusantara of Law and Politic Review, 2026)
Advances in healthcare technology have significantly improved the quality of medical services through the increasing use of sophisticated medical devices. However, medical device failures may cause substantial harm to patients, including the rejection of health insurance claims, thereby creating complex legal issues regarding the allocation of liability among hospitals, medical device vendors, and health insurance companies. This study aims to analyze the legal responsibilities of hospitals and medical device vendors for medical device failures that result in patient losses and the rejection of health insurance claims under the Indonesian health law framework. It also seeks to formulate an ideal legal framework for the allocation of responsibilities among the relevant parties to ensure fair legal protection for patients. This research employs a normative legal research method using statutory, conceptual, and analytical approaches. Legal materials were collected through library research, including legislation, legal literature, and scholarly journals, and were analyzed qualitatively using a descriptive-analytical method. The findings indicate that hospitals bear legal responsibility under the doctrine of corporate liability to ensure the safety, quality, and proper management of medical devices used in healthcare services. Medical device vendors are liable under the principle of product liability for product defects, technical failures, and negligence in maintenance and after-sales services. Meanwhile, health insurance companies are obligated to process and settle claims in accordance with the principle of utmost good faith and may not reject claims arbitrarily without conducting an objective investigation into the cause of the loss. This study concludes that Indonesia requires a more comprehensive legal framework governing the allocation of responsibilities through an integrated investigation mechanism that promotes legal certainty, justice, accountability, and effective legal protection for patients as the most vulnerable parties in healthcare services.